BERAT POTONG DAN BAGIAN OFFAL EXTERNAL ITIK BALI JANTAN YANG DIBERI PAKAN KOMERSIAL DISUBSTITUSI POLLAR DAN ADITIF ”DUCK MIX” - Wiradhana, Agus Putu; Siti, Ni Wayan; Ariana, I Nyoman Tirta (Jurnal Peternakan Tropika, 2014)
This study to determine the effect of substitution and addition pollard duck mix in the commercial ration, the weight cut and the external offal of ducks Bali age of ten weeks. Ducks fed 100% commercial as treatment A (control), ducks fed commercial pollard 85% + 15% + 0.3% duck mix as treatment B, ducks fed a commercial 70% + 30% + pollard "Duck Mix "0.3% as treatment C, and the ducks are fed a commercial 55% + 45% + pollard" Duck Mix '0.3% as treatment D. The results weight cut duck who gives 100% commercial ration as control 1558.60 tail, whereas treatment B, C, D has a 2.09% cut weight, 5.09%, 5.08% was not significant (P> 0, 05) lower than the control. Heavy duck head on the perpetrator A 5.30%, while B 5.28% C 2.45% D 2.45%, 1.70% D unreal, lower than the control. Heavy neck duck on treatment A 8,, 09% while B 4.57%, C 10.26%, 0.37% D unreal, higher than the control. Heavy duck leg on treatment A 2.49%, 6.83%, while B, C 10.04% D 12.45% is not real, lower than the control. Treatment duck feather weight at a 6.71%, while 6.71% B, while B 0.60%, 7.30% and D is not significantly higher and 1.04% C handles not significant lower than the control. Based on the results of the study concluded that administration pollard 15%, 30% and 45% as a substitute as feed additives commercial with "Duck Mix" produce weight cut and the external offal Bali male ducks were not different from control.   Key words :  Weight Cut, Ducks, Offal External, Pollard, Ration
Keywords: Weight Cut, Ducks, Offal External, Pollard, Ration